Digital Thought Balloons: Electronic Delivery and the Comic Book. - Cadieux, Lee (International Journal of the Book, 2011)
Digital Thought Balloons explores emerging modes of electronic delivery for Manga, BD (Bande Desinee) and Comic Books. iPhone apps such as iVerse, XComics, CanalBD, and Manga Rocks allow users to access this type of visual material on mobile and hand held devices. The iPad, remarkably similar in size to the classic American Comic Book, opens the market further by allowing its users to run these same applications on a much larger screen, since the iPad allows users to view full color, image-based work, such as Comic Books, BD and Manga as well text-based eBooks. Amazon's Kindle with its inherent display limitations, offers no such flexibility. The App store offers global distribution to independent publishers and mass market moguls alike through its egalitarian structure, attractive to both niche market and main stream communities. Stand alone material may be purchased with embedded viewer applications or through the applications themselves. It remains to be seen whether these new modes of electronic delivery pose a threat to the physical artefact of the Comic Book or merely provide alternative methods of accessing this vibrant medium.